PRESENTASI DIRI MAHASISWA SEBAGAI SEXY DANCER CLUBBING DI KOTA SURABAYA (Studi Dramaturgi Presentasi Diri Mahasiswa sebagai Sexy Dancer Club Malam di Kota Surabaya) - Wahyuni, Putri; Dewi,S.Sos.,M.Med.Kom, Putri Aisyiyah Rachma (The Commercium, 2023)
This thesis examines the phenomenon of self-identity displayed by students as sexy dancers. A side profession that adds income and becomes a place to channel the hobby of dancing. Students with a profession as a night club sexy dancer, play various roles and take relevant identities to define something they want to highlight. There are several symbols included in self-presentation which can be in the form of non-verbal communication that can be used to strengthen the identity of the role being played at that time. The purpose of this thesis is to find out the phenomenon of self-identity of sexy dancers, the majority of whom are students with a high educational background. This thesis uses a qualitative method with data collection techniques of interviews, observations and observations of 4 informants. The theory used in this thesis is Erving Goofman's Dramaturgy theory. The results of the study show that the front stage life of a sexy dancer performs her role in an all out or professional manner, performed powerfully, using make up, sexy costumes assisted by a setting of sparkling lights according to the existing lighting. Meanwhile, backstage, he presented himself but in a more relaxed version, not using thick makeup, sexy costumes, just dressed like a normal student, also joined in certain communities to socialize more broadly.